2021
DOI: 10.1002/ange.202110441
|View full text |Cite
|
Sign up to set email alerts
|

Phenoxy Radical‐Induced Formation of Dual‐Layered Protection Film for High‐Rate and Dendrite‐Free Lithium‐Metal Anodes

Abstract: The uncontrollable dendrite growth of Li metal anode leads to poor cycle stability and safety concerns, hindering its utilization in high energy density batteries. Herein, a phenoxy radical Spiro‐O8 is proposed as an artificial protection film for Li metal anode owing to its excellent film‐forming capability and remarkable ionic conductivity. A spontaneous redox reaction between the Spiro‐O8 and Li metal results in the formation of a uniform and highly ionic conductive organic film in the bottom. Meanwhile, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 60 publications
0
8
0
Order By: Relevance
“…The reason of using carbon cloth as matrix is that the three-dimensional (3D) structure of carbon cloth can not only offer a stable host for Li plating/stripping to signi cantly mitigate the volume change of electrode during cycling [34][35][36] , but also provide the possibility for the industrialization of 3D Li-C composite anode due to the convenience of processing 37 . Some previous studies have shown that the cycle stability of Li metal anode in a full cell is worse than that in the symmetrical cell 14,38,39 . Accordingly, we evaluated the electrochemical performance of t-Li 2 ZrF 6 -rich SEI in Li-C||LPF full cells rather than symmetrical cells.…”
mentioning
confidence: 96%
“…The reason of using carbon cloth as matrix is that the three-dimensional (3D) structure of carbon cloth can not only offer a stable host for Li plating/stripping to signi cantly mitigate the volume change of electrode during cycling [34][35][36] , but also provide the possibility for the industrialization of 3D Li-C composite anode due to the convenience of processing 37 . Some previous studies have shown that the cycle stability of Li metal anode in a full cell is worse than that in the symmetrical cell 14,38,39 . Accordingly, we evaluated the electrochemical performance of t-Li 2 ZrF 6 -rich SEI in Li-C||LPF full cells rather than symmetrical cells.…”
mentioning
confidence: 96%
“…3,4 For protecting the environment and achieving the purpose of sustainable development, the development and utilization of new energy are urgently needed. 5,6 Efficient energy storage has been an important bridge for reconciling the immediate quantity of electricity supply and demand, 7,8 so it is necessary to develop an efficient and green secondary energy storage system. 9,10 LIBs are widely used because of their high specific capacity and high security.…”
Section: Introductionmentioning
confidence: 99%
“…Energy and sustainable development remain the main concerns of all countries in the 21st century. , However, the use of fossil fuels has resulted in many environmental problems, such as increased smog, intensified greenhouse effect, frequent acid rain, and so on. , For protecting the environment and achieving the purpose of sustainable development, the development and utilization of new energy are urgently needed. , Efficient energy storage has been an important bridge for reconciling the immediate quantity of electricity supply and demand, , so it is necessary to develop an efficient and green secondary energy storage system. , LIBs are widely used because of their high specific capacity and high security. , For the current increasing demand, the existing LIBs have been difficult to meet, so it is necessary to develop a new generation of LIB electrode material. , …”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, with the ever‐increasing demand for LIBs, it is urgently important to construct novel electrode material with high‐performance Li storage and high‐capacity 1–3 . Previous works are mainly concentrated on inorganic compounds (such as transition metal oxide, metal phosphate, sulfide, graphite, P, and Si) as the cathode or anode 4–8 . However, these electrode materials have several defects, including intricate preparation procedure, high toxicity, high‐cost, rapid capacity decay due to their volume expansion during the discharge process 9–11 .…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3] Previous works are mainly concentrated on inorganic compounds (such as transition metal oxide, metal phosphate, sulfide, graphite, P, and Si) as the cathode or anode. [4][5][6][7][8] However, these electrode materials have several defects, including intricate preparation procedure, high toxicity, high-cost, rapid capacity decay due to their volume expansion during the discharge process. [9][10][11] This is to the disadvantage of practical application of LIBs.…”
Section: Introductionmentioning
confidence: 99%